2002
DOI: 10.12930/0271-9517-22.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Techniques and Interventions of Solution-Focused Advising

Abstract: Solution-focused advising is a novel method for engaging students in the advising process. In NACADA Journal 22(1), we discussed a conceptual framework for understanding the integration of solution-focused therapy into academic advising of undecided students (Mayhall & Burg, 2002). In this article we expand on the introduction by providing specific information on the skills used in solution-focused advising. The techniques of goal setting, scaling questions, presuppositional questions, the miracle question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
(2 reference statements)
1
3
0
Order By: Relevance
“…Supporting the description of the research results, (Fanaei, Gorji, & Abedi, 2014) in their research report revealed that SFC is effective in increasing internal and external learning motivation in students in Iran. This research finding was support by the result conducted by Lewis & Osborn (2004) and Burg and Mayhall (2002) that SFC was a novel method for engaging students motivation. Ermawati (2010) in her research also said that therapy focuses on solutions increased learning motivation in Class X of high school students.…”
Section: Group Analysissupporting
confidence: 81%
“…Supporting the description of the research results, (Fanaei, Gorji, & Abedi, 2014) in their research report revealed that SFC is effective in increasing internal and external learning motivation in students in Iran. This research finding was support by the result conducted by Lewis & Osborn (2004) and Burg and Mayhall (2002) that SFC was a novel method for engaging students motivation. Ermawati (2010) in her research also said that therapy focuses on solutions increased learning motivation in Class X of high school students.…”
Section: Group Analysissupporting
confidence: 81%
“…The main assumptions and techniques concerning the solution-focused approach have been broadly discussed in numerous publications written by the creators and practitioners of sFa (de shazer, 1984, 1985, 1992proudlock, 2017;de shazer et al, 2007;de Jong, berg, 2007;berg, de shazer, 1993;berg, dolan, 2001;Franklin, bolton, 2014;burg, Mayhall, 2002;pichot, dolan, 2003) and they can be summarized as follows:…”
Section: Research Aimmentioning
confidence: 99%
“…specific situations and contexts in which a variety of sFa tools are applicable can be found in the following guidebooks: Solution-Focused Practice -a Toolkit for Children & Young People, edited by bazalgette and collaborators (2014), offers some ready-made exercises that could be used when working with the clients; and The Advisor's Toolbox. Techniques and Interventions of Solution-Focused Advising edited by burg, and Mayhall (2002) that offers a compilation of sFa tools.…”
Section: Research Aimmentioning
confidence: 99%
“…They can also ask students what they have always wanted to do or what they would do if all constraints ceased to exist. This approach is similar to Burg and Mayhall's (2002) -miracle question‖ (p. 82) that leads students to explore possibilities they have not previously considered. Each of these lines of questioning can be effective ways of gaining insight into students' areas of strength.…”
Section: Laurie Schreiner Andchip Andersonmentioning
confidence: 99%